P152 The effect of T-lymphocytes and tumor-associated macrophages on invasion of peritoneal metastases of epithelial ovarian cancer. (1st November 2019) - van Baal, J; Lok, C; Jordanova, K; van Driel, W; Amant, F; Horlings, H; van de Vijver, K
Abstract : Introduction/Background: Peritoneal metastases of advanced high-grade serous ovarian cancer (HGSOC) are small-sized tumor depositions with superficial growth towards the peritoneal cavity, rather than invading deeper layers. It is unknown whether depth of peritoneal invasion beyond the peritoneal elastic lamina (PEL) is of prognostic relevance and if the peritoneal tumormicroenvironment (TME) plays a role in this invasion. We explored the integrity of PEL in peritoneal metastases of HGSOC, the composition of TME, and the association with progression-free survival (PFS) and overall survival (OS). Methodology: .Peritoneal metastases of 69 patients with HGSOC were consecutively collected during primary or interval cytoreductive surgery. Clinical data were collected from medical charts. To evaluate the integrity of PEL with regard to depth of tumor invasion we stained whole slides with histochemistry. To assess the composition of TME, T cell- (CD3, CD8) and M2-macrophage markers (CD163) were analyzed. Intraepithelial and stromal immune cells were scored on whole slide sections using algorithms created in Definiens Tissue studio. Results: During follow-up, 64 patients (92.8%) had recurrent disease and 54 patients (78.3%; median survival 28.6 months) had died. In 39 patients (56.5%) a disrupted PEL was observed (figure 1). These patients more often had residual disease after cytoreductive surgery (p=0.050). Integrity of PEL was not correlated with PFS or OS. An intact PEL was associated with higher densities of intraepithelial (ie)CD8+ cells. Abundance of ieCD3+ cells, stromal (s)CD3+ cells and sCD8+ cells was associated with PFS and OS (table 1). M2-macrophage infiltration was not correlated with PFS or OS. Conclusion: High density of CD3+ and CD8+ cells in peritoneal metastases of HGSOC is associated with increased PFS and OS, independent of PEL integrity. These results suggest that these immune cells promote a tumor-suppressive microenvironment and may function as prognostic biomarkers for survival, and perhaps as predictive biomarker for immunotherapy response. Disclosure: Nothing to disclose.